2011
DOI: 10.1089/ars.2011.3965
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Weakness and Fatigue in Skeletal Muscle: The Role of Oxidative Stress

Abstract: Significance: Fatigue is one of the most common symptoms of cancer and its treatment, manifested in the clinic through weakness and exercise intolerance. These side effects not only compromise patient's quality of life (QOL), but also diminish physical activity, resulting in limited treatment and increased morbidity. Recent Advances: Oxidative stress, mediated by cancer or chemotherapeutic agents, is an underlying mechanism of the drug-induced toxicity. Nontargeted tissues, such as striated muscle, are severel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
224
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(238 citation statements)
references
References 259 publications
7
224
1
6
Order By: Relevance
“…These combined results suggest that 5-FU might affect the loss of skeletal muscle, although the precise mechanism is unknown. Another anticancer agent, doxorubicin, has recently been shown to cause a catabolic response in skeletal muscle through oxidative stress by elevating the serum levels of inflammatory cytokines, especially tumor necrosis factor (TNF), resulting in a loss of skeletal muscle mass leading to weakness and fatigue [28]. One study reported delayed skeletal muscle dysfunction in survivors of childhood acute lymphoblastic leukemia, in which repeated administration of combination chemotherapy drugs (e.g., vincristine, glucocorticoids, doxorubicin, methotrexate, asparaginase) was strongly implicated [29].…”
Section: Discussionmentioning
confidence: 99%
“…These combined results suggest that 5-FU might affect the loss of skeletal muscle, although the precise mechanism is unknown. Another anticancer agent, doxorubicin, has recently been shown to cause a catabolic response in skeletal muscle through oxidative stress by elevating the serum levels of inflammatory cytokines, especially tumor necrosis factor (TNF), resulting in a loss of skeletal muscle mass leading to weakness and fatigue [28]. One study reported delayed skeletal muscle dysfunction in survivors of childhood acute lymphoblastic leukemia, in which repeated administration of combination chemotherapy drugs (e.g., vincristine, glucocorticoids, doxorubicin, methotrexate, asparaginase) was strongly implicated [29].…”
Section: Discussionmentioning
confidence: 99%
“…These treatments lead to a decrease in QoL, physical activity and enhance their morbidity [10]. Cancer-related fatigue (CRF), which is frequently reported by cancer patients, is defined as an unusual and persistent sense of tiredness, affecting both physical and mental capacity and is unrelieved by rest [35].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C is a potent antioxidant and acts as a cofactor for numerous biosynthetic and regulatory enzymes in the body [5] , which may account for its observed effects in this case. Oxidative stress has been implicated in chronic fatigue syndrome [11] and chemotherapy-related fatigue [12] . Parenteral vitamin C has been shown to decrease both cancer -and chemotherapyrelated fatigue in cancer patients [2] .…”
Section: Discussionmentioning
confidence: 99%